Monument und Inschrift : gesammelte Aufsätze zur senatorischen Repräsentation in der Kaiserzeit - Eck, Werner (Beiträge zur Altertumskunde ;, 2010)
One of the most important forms of senatorial representation was a monument embellished with an inscription. Both - inscription and monument - were always intimately related, so that epigraphy and the study of ancient history are challenged to work more closely with archaeology. Only in this way is it possible to establish a correct understanding of how senators represented themselves. Therefore, the articles collected in this volume create, among other things, the basis for a new viewpoint of the social and cultural history of the senatorial order under the Roman Empire.